Revisiting innovation leadership - Alsolami, Hazaz Abdullah; Teoh, Kenny Guan Cheng; Ibn Twalh, Abdulaziz Awad (Scientific Research Publishing, 2016)
Innovation leaders must possess multiple attributes in order to effectively manage the increasing demands for innovation in many facets of business organizations, especially in influencing creativity and innovation. Research findings have indicated that the behaviours of innovation leaders differ from the leadership behaviours that are deemed sufficient in conventional leadership situations. However, the literature on leadership suggests that there remains a research gap—what are the attributes required of successful innovation leaders?—That warrants a study to determine more precisely what those attributes are. A review of the current literature indicated that innovation leadership is a multi-leadership phenomenon consisting, inter alia, of charismatic leadership, transformational leadership and innovation leadership attributes and competencies. This paper discussed the innovation leadership attributes as portrayed in the literature, thereby providing a firm, structural foundation for researching the components of innovation leadership and providing insights to define the construct and, ultimately, to develop a psychometric measure.